A pair of polymorphous metal–organic frameworks based on an angular diisophthalate linker: synthesis, characterization and gas adsorption properties. Issue 3 (8th December 2017) - Chen, Fengli; Bai, Dongjie; Wang, Yao; He, Minghui; Gao, Xiaoxia; He, Yabing
Abstract : A pair of polymorphous MOFs derived from a bent diisophthalate ligand were synthesized by modulating solvothermal conditions, exhibiting comparable gas adsorption properties with respect to C2 H2, CO2 and CH4 . Abstract : The combination of an angular diisophthalate ligand, 5, 5′-(naphthyl-2, 7-yl)diisophthalate (H4 L), and copper ions under different solvothermal conditions afforded two polymorphous metal–organic frameworks (ZJNU-77 andZJNU-78 ) with the same framework composition of [Cu2 (L)(H2 O)2 ], providing a platform to investigate the relationship between MOF polymorphism and gas adsorption properties. As determined by single-crystal X-ray diffraction, ZJNU-77 andZJNU-78 exhibited three-dimensional networks crystallizing in different space groups. Their structural differences were mainly manifested by the ligand's conformation, the level of framework interpenetration and the network's topology. Interestingly, gas adsorption studies showed that the two compounds after desolvation displayed comparable gas adsorption properties with respect to C2 H2, CO2 and CH4, despite their different surface areas and pore volumes. The C2 H2, CO2, and CH4 uptake capacities at 298 K and 1 atm are 120.2, 78.1, and 18.4 cm 3 (STP) g −1 forZJNU-77, and 122.0, 82.0, and 18.9 cm 3 (STP) g −1 forZJNU-78, respectively. The IAST adsorption selectivities for the equimolar C2 H2 /CH4 and CO2 /CH4 mixtures are 28.6 and 5.7 forZJNU-77, and 28.4 and 5.9 forZJNU-78 at 298 K and 1 atm. These results indicate that besides the surface area, the pore size also plays a crucial role in gas adsorption. This work not only represents an intriguing example of MOF polymorphism achieved by controlling solvothermal conditions, but also provides an insight into the correlation between MOF polymorphism and gas adsorption properties.